Financial Literacy Education in Ontario: An Exploratory Study of Elementary Teachers’ Perceptions, Attitudes, and Practices - Henderson, Gail E.; Beach, Pamela; Coombs, Andrew (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2021)
Politicians are pushing school boards to do more to ensure students leave school with the financial literacy skills they will need to navigate an increasingly complex financial marketplace. Financial literacy education must start early to achieve this goal, yet there has been very little Canadian research on financial literacy education at the elementary level. This exploratory study used an anonymous, online survey to gain a preliminary understanding of full-time Ontario elementary teachers’ perceptions, attitudes, and practices with respect to financial literacy education. Respondents overwhelmingly favour teaching financial literacy in elementary school. Almost half of respondents currently incorporate financial literacy into their classroom practice. These teachers rely primarily on free, online resources. With respect to barriers to teaching financial literacy, respondents cited the lack of an appropriate curriculum and lack of support from schools and school boards. Respondents identified professional development as the main type of support they would like to see schools and school boards provide to support them in teaching financial literacy going forward.